2015
DOI: 10.18393/ejss.2015.3.161-168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of poultry litter biochar on soil enzyme activities and tomato, pepper and lettuce plants growth

Abstract: Biochar application to soils is being considered as a means to sequester carbon (C) while concurrently improving soil functions. A greenhouse experiment was carried out to determine the effects of biochar from the pyrolysis poultry litter (PL) on the soil enzyme activities, organic matter content and growth of tomato, pepper and lettuce plants. In the experiment, the combination of 15.15.15 composite fertilizer with 0, 200, 400 and 600kg/da doses of PL biochar were applied into the clay loam soil. Compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Soil microbes play a key role in decomposition of the organic matter via a variety of soil enzymes. Therefore, application of biochar and manure is a method of replenishing degraded soil health by improving the biological status of the soil, which usually implies an increase in microbial and enzyme activities (Akça & Namli, ; Albiach, Canet, Pomares, & Ingelmo, ; Burns et al, ; Francioli et al, ; Ouyang, Tang, Yu, & Zhang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Soil microbes play a key role in decomposition of the organic matter via a variety of soil enzymes. Therefore, application of biochar and manure is a method of replenishing degraded soil health by improving the biological status of the soil, which usually implies an increase in microbial and enzyme activities (Akça & Namli, ; Albiach, Canet, Pomares, & Ingelmo, ; Burns et al, ; Francioli et al, ; Ouyang, Tang, Yu, & Zhang, ).…”
Section: Introductionmentioning
confidence: 99%
“…The results from numerous tests have shown that biochars may increase the content of soil organic matter, and in particular extracted organic carbon [16]. In addition, they may increase the biomass of soil microorganisms and stimulate their enzymatic activity [12,17]. In the longer term, the beneficial effects of biochar application in the soil decide on its fertility and productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Lehmann and Joseph (2012) have distinguished the term biochar from charcoal in that it is charred organic matter that is applied to soil not only to improve soil properties but also to promote soil remediation or other environmental services while the charcoal is used as fuel or source of heat, as a filter, as a reductant in iron-making or as a colouring agent in industry or art. Researches on biochar are expanding rapidly not only because of its potential for carbon sequestration (Sohi and Shackley, 2009) but also for its several co-benefits as soil amendment, such as increase in crop yield (Akca and Namli, 2015), potential as a technology for immobilizing pollutants (Herath et al, 2015) and increasing soil fertility and nutrient retention in soils. Though previous researchers have really explored the potentials of biochar as soil amendments for agricultural production and improvement of soil quality (Ndor et al, 2015), research on accurate rate of biochar application on a degraded Ultisol and other soil types for specific arable crops is scanty and rather proceeding slowly.…”
Section: Introductionmentioning
confidence: 99%